Fuzzy Analysis Determining The Criteria of Recipients for Liable Housing Using Sugeno Method - Rika Widya Perdana (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
The house is the most important part in human life, a comfortable home will produce peace of mind and soul to carry out daily life. Currently, many rural communities have houses in poor conditions or are not suitable for occupancy, so the government provides housing assistance to be repaired to make it better and more durable. The problem that occurs is that there is no knowledge system in determining people who are entitled to housing assistance according to predetermined criteria. The purpose of this study is to help make it easier to select the right community to receive assistance in the form of a system. The settlement of this case uses the Sugeno method with the output results in the form of values 0 and 1. The variables used in this study are 4, namely family cards, identity cards, land ownership rights and house conditions, output in the form of systems in decision making.